The OECD report on regulatory reform: synthesis (Paris, 1997)
"This book shows hows how regulatory reform has produced substantial economic and social benefits for citizens by enhancing competition and reducing regulatory costs. It can boost efficiency, sharply reduce prices, stimulate innovation, and improve the ability of economies to adapt to change and remain competitive in global markets. Properly done, regulatory reform also can help governments promote other important policy goals, such as environmental quality, health, and safety. Finally, country experience shows that disruptions which can accompany reform can be addressed by complementary policies and actions. In this Report, the OECD calls for renewed attention to regulatory reform, and the recommendations in this Report constitute an ambitious plan for action. In May 1997, Ministers of OECD countries welcomed this Report and agreed to work to implement its recommendations in their countries.